Risk factors of hypertension in Expo South Sulawesi participants - Syahratul Aeni; Nildawati Nildawati; Surahmawati Surahmawati (Al-Sihah : The Public Health Science Journal, 2020)
Epidemiological transition is marked by changes in the pattern of disease and death which was originally dominated by infectious diseases that turn to non-communicable diseases, one of which is hypertension. In Indonesia, hypertension is a potential problem, in addition to its high prevalence, as well as its fatal diseases such as heart disease, stroke, kidney failure and others. The purpose of this study was to determine the risk factors that influence hypertension. This research used quantitative research with observational analytic approach and cross sectional study design. The population in this study was South Sulawesi expo participants. The sample in this study was 107 respondents with a purposive sampling method. The results of this study indicated that there was a significant relationship between family history of disease factors with hypertension but there was no significant correlation between the incidence of hypertension with some participant behavior such as smoking habits, lack of physical activity, less consumption of fruits and vegetables, and alcohol comsumtion. Although some trigger factors are not significant for hypertension, these factors can cause and worsen the occurrence of hypertension in the future. We suggest that expo participants always check their blood pressure routinely